2010
DOI: 10.1029/2009jb006302
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of oxygen between the Earth's mantle and core

Abstract: [1] Experiments to investigate the partitioning of oxygen between liquid iron and (Mg,Fe)O magnesiowüstite were conducted at 30-70 GPa and 2800-3500 K using a laser-heated diamond anvil cell. A thin foil was prepared from the reacted regions in the recovered samples using a focused ion beam. The compositions of coexisting quenched iron and magnesiowüstite were measured using a transmission electron microscope equipped with energy dispersive X-ray spectroscopy and electron energy-loss spectroscopy. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
112
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 61 publications
(119 reference statements)
15
112
1
Order By: Relevance
“…We also ran 15 experiments in a multianvil press at pressures of 15 (Frost et al, 2010) results in a value that is higher by ~0.4 log units, in agreement with previous studies (e.g., Cottrell et al, 2009;Siebert et al, 2011).…”
Section: Multianvil Press Experiments and Analysessupporting
confidence: 89%
See 2 more Smart Citations
“…We also ran 15 experiments in a multianvil press at pressures of 15 (Frost et al, 2010) results in a value that is higher by ~0.4 log units, in agreement with previous studies (e.g., Cottrell et al, 2009;Siebert et al, 2011).…”
Section: Multianvil Press Experiments and Analysessupporting
confidence: 89%
“…Incorporating activities for Fe and FeO that differ from unity based on a thermodynamic model (Frost et al, 2010) results in a calculated oxygen fugacity that is higher by ~0.4 log units, in agreement with previous studies Siebert et al, 2012). Two experiments were run at almost identical conditions, with the only difference being the silicon content of the metal.…”
Section: Diamond Anvil Cell Experimentssupporting
confidence: 69%
See 1 more Smart Citation
“…While the proposed reaction products have not been found in later studies 85 , recent experiments have shown that the lowermost mantle may be depleted in FeO due to the loss to the oxygen-undersaturated outer core [85][86][87][88] . Addition of oxygen to the core could have been provided by an oxidized lower mantle basal magma ocean early in Earth's history 88 .…”
Section: Anti-correlated Wave Speedsmentioning
confidence: 94%
“…Because the inner core is growing from the outer core, and these are in chemical equilibrium, then the outer core should also contain silicon, between 1.2 and 3.6% [assuming a liquid/ solid partition coefficient (7) of 1.5 ± 0.3 for silicon]. Moreover, core formation experiments place a tight constraint (12,(31)(32)(33)(34)(35) on oxygen solubility in molten iron: incorporating large amounts of oxygen in a core-forming metal in equilibrium with a molten silicate requires very high temperatures. In those conditions, silicon will always be incorporated in the metal as well (31,34,35).…”
mentioning
confidence: 99%